Treatment of Helicobacter pylori Infection in Patients with Penicillin Allergy - Ligang Liu; Milap C. Nahata (MDPI AG, 2023)
Helicobacter pylori is among the prevalent causes of infections worldwide, and its resistance rate to antibiotics has been rising over time. Amoxicillin is the cornerstone for the treatment regimen. However, the prevalence of penicillin allergy ranges from 4% to 15%. In patients with true allergy, Vonoprazan-Clarithromycin-Metronidazole and bismuth quadruple therapy have demonstrated excellent eradication and high adherence rates. Vonoprazan-based therapy is administered less frequently and may be better tolerated than bismuth quadruple therapy. Therefore, vonoprazan-based therapy may be considered as a first-line therapy if accessible. Bismuth quadruple therapy can be used as the initial therapy when vonoprazan is unavailable. Levofloxacin or sitafloxacin-based regimens achieve a moderately high eradication rate. However, these are associated with potentially serious adverse effects and should only be used when other effective and safer regimens are unavailable. Cephalosporins such as cefuroxime have been used as an alternative to amoxicillin. Microbial susceptibility studies can guide the selection of appropriate antibiotics. PPI-Clarithromycin-Metronidazole fails to achieve a high eradication rate and should be used as a second-line therapy. PPI-Clarithromycin-Rifabutin should not be used because of low eradication rate and frequent adverse reactions. The choice of the most effective antibiotic regimen can enhance clinical outcomes in patients with H. pylori infection and penicillin allergy.